Bibliometrics Analysis and Future Study Trends in Anaerobic Biofilter Systems for Laundry Wastewater Treatment - Sutrisno, Joko; Kholif, Muhammad Al (International Journal of Marine Engineering Innovation and Research, 2025)
The rapid expansion of the laundry industry, particularly in residential areas, has led to significant environmental challenges due to the discharge of untreated wastewater containing high levels of pollutants, such as Chemical Oxygen Demand (COD) and phosphate (PO4). This study aims to explore the effectiveness of anaerobic biofilter systems in reducing COD and PO4 levels in laundry wastewater. A lab-scale anaerobic biofilter reactor was designed and operated at varying hydraulic retention times (HRTs) of 9, 11, and 13 hours to treat the wastewater. The results showed that the anaerobic biofilter system effectively reduced PO4 levels, meeting Indonesian regulatory standards, with the highest removal efficiency observed at an HRT of 11 hours. However, while COD levels were reduced, they remained above the required quality standards, indicating the need for optimization of the treatment process. The study highlights the potential of anaerobic biofilters in laundry wastewater treatment and suggests further research into integrated treatment approaches for improved pollutant removal.